Advanced potentiometry : potentiometric titrations and their systematic errors - Néher-Neumann, Erzsébet (Dordrecht : Springer, 2009)
"Advanced Potentiometry" details the accurate calculation of potentiometric titrations. Additional terms such as the ideal diffusion potential together with the contribution of activity factors furnish calculated stability constants which do not include systematic errors and thus present a complete and correct description of equilibrium processes. Moreover, serious systematic errors resulting from the recent use of curve-fitting computer programs are highlighted later in the text. "Advanced Potentiometry" can advantageously be used by lecturers, researchers, PhD graduates and undergraduate students working in the fields of Solution Chemistry, Physical Chemistry, Inorganic Chemistry and Analytical Chemistry and Environmental Research.
Tambien disponible en formato EPUB
Keywords: POTENCIOMETRÍA